2010
DOI: 10.1186/1476-4598-9-175
|View full text |Cite
|
Sign up to set email alerts
|

p21 promotes oncolytic adenoviral activity in ovarian cancer and is a potential biomarker

Abstract: The oncolytic adenovirus dl922-947 replicates selectively within and lyses cells with a dysregulated Rb pathway, a finding seen in > 90% human cancers. dl922-947 is more potent than wild type adenovirus and the E1B-deletion mutant dl1520 (Onyx-015). We wished to determine which host cell factors influence cytotoxicity. SV40 large T-transformed MRC5-VA cells are 3-logs more sensitive to dl922-947 than isogenic parental MRC5 cells, confirming that an abnormal G1/S checkpoint increases viral efficacy. The sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…These data indicated that p21 expression was associated with adenoviral E1A mediated antitumor activity. Although there were publications showed that p21 expression reduced oncolytic adenovirus activity in tumor cells [29], our data was identical with the reports that p21 overexpression appeared an important factor in elevating anti-tumor activity mediated by adenoviral E1A [30]. …”
Section: Discussionsupporting
confidence: 91%
“…These data indicated that p21 expression was associated with adenoviral E1A mediated antitumor activity. Although there were publications showed that p21 expression reduced oncolytic adenovirus activity in tumor cells [29], our data was identical with the reports that p21 overexpression appeared an important factor in elevating anti-tumor activity mediated by adenoviral E1A [30]. …”
Section: Discussionsupporting
confidence: 91%
“…The sensitivity of cancer cell lines to the oncolytic adenovirus dl922-947 varies considerably, even in cells with similar infectivity (8). TOV21G, IGROV1, and A2780CP are 3 ovarian cancer cell lines that cover a range of sensitivities, with IC 50 values varying over 3 log scales ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that expression of p21 in ovarian cancer is a marker for a host cell environment conducive to the expression of E1A (8). E1A is the first viral gene to be expressed after infection, and its expression correlates with cellular sensitivity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Another oncolytic virus (vesicular stomatitis virus) as well as HDAC inhibitors showed synergistic interaction by dampening the innate immunity towards the oncolytic virus (13,19). In another report, transfection of p21 promoted oncolytic adenoviral activity in ovarian cancer by increasing E1A expression (20).…”
Section: Introductionmentioning
confidence: 96%